Governance of the Exploration of Subglacial Antarctica - Siegert, Martin John; Kennicutt, Mahlon C. (Frontiers in Environmental Science, 2018)
Subglacial lakes, and their surrounding aqueous environments, are known to be viable yet extreme habitats for microbial life that may hold records of climate change spanning hundreds of thousands of years. Since the detection of Lake Vostok in 1996 plans have been developed to access, sample and monitor these unique environments. Critical to these plans is assurance that contamination and disturbance is minimized in all aspects of the activity. Precisely how this is achieved has been a matter of international debate for many years culminating in the formulation of a ‘Code of Conduct’ to guide responsible scientific exploration and stewardship of these pristine systems by the Scientific Committee on Antarctic research. The Code of Conduct was first introduced to the Antarctic Treaty Consultative Meeting in 2011, influencing planning for three exploration programmes. In May 2018, following several recent and operational advances, Antarctic Treaty Parties agreed to its use and dissemination, ensuring that subglacial lakes exploration and access is undertaken in a responsible, defensible and fact-based manner. As our knowledge of subglacial lakes improves, so too will our appreciation of their scientific value and potential vulnerability. In other regions of Antarctica where value and vulnerabilities are high, Antarctic Specially Protected Areas and Antarctic Specially Managed Areas ensure long-term protection whilst allowing scientific access and study. Such governance models will be applicable to the conservation and protection of subglacial lake systems as scientific understanding of their form and functioning advances.